Photoredox catalysis via consecutive 2LMCT- and 3MLCT-excitation of an Fe(iii/ii)–N-heterocyclic carbene complex. Issue 32 (2nd August 2022) - Ilic, Aleksandra; Schwarz, Jesper; Johnson, Catherine; de Groot, Lisa H. M.; Kaufhold, Simon; Lomoth, Reiner; Wärnmark, Kenneth
Abstract : An iron complex with N-heterocyclic carbene ligands engages in efficient photoredox catalysis via excited state electron transfer reactions of its Fe(ii ) and Fe(iii ) oxidation states. Abstract : Fe–N-heterocyclic carbene (NHC) complexes attract increasing attention as photosensitisers and photoredox catalysts. Such applications generally rely on sufficiently long excited state lifetimes and efficient bimolecular quenching, which leads to there being few examples of successful usage of Fe–NHC complexes to date. Here, we have employed [Fe(iii )(btz)3 ] 3+ (btz = (3, 3′-dimethyl-1, 1′-bis( p -tolyl)-4, 4′-bis(1, 2, 3-triazol-5-ylidene))) in the addition of alkyl halides to alkenes and alkynes via visible light-mediated atom transfer radical addition (ATRA). Unlike other Fe–NHC complexes, [Fe(iii /ii )(btz)3 ] 3+/2+ benefits from sizable charge transfer excited state lifetimes ≥0.1 ns in both oxidation states, and the Fe(iii ) 2 LMCT and Fe(ii ) 3 MLCT states are strong oxidants and reductants, respectively. The combined reactivity of both excited states enables efficient one-electron reduction of the alkyl halide substrate under green light irradiation. The two-photon mechanism proceeds via reductive quenching of the Fe(iii ) 2 LMCT state by a sacrificial electron donor and subsequent excitation of the Fe(ii ) product to its highly reducing 3 MLCT state. This route is shown to be more efficient than the alternative, where oxidative quenching of the less reducing Fe(iii ) 2 LMCT state by the alkyl halide drives the reaction, in the absence of a sacrificial electron donor.